2013
DOI: 10.1161/circulationaha.112.001238
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue Potentiates Contraction of Coronary Vascular Smooth Muscle

Abstract: Background This investigation examined the mechanisms by which coronary perivascular adipose tissue (PVAT)-derived factors influence vasomotor tone and the PVAT proteome in lean vs. obese swine. Methods and Results Coronary arteries from Ossabaw swine were isolated for isometric tension studies. We found that coronary (P=0.03) and mesenteric (P=0.04), but not subcutaneous adipose tissue, augmented coronary contractions to KCl (20 mM). Inhibition of CaV1.2 channels with nifedipine (0.1 μM) or diltiazem (10 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
124
2
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 48 publications
15
124
2
3
Order By: Relevance
“…In the present study, LAD coronary arteries obtained from obese OS had attenuated contraction to KCl and PGF 2␣ compared with Yorkshire nonischemic lean control swine with no significant difference between CLI ϩ SR-nitrite-and CLI ϩ placebo-treated groups. Similar to our findings, Owen et al (38) concluded that obesity augments Ca 2ϩ cycling and smooth muscle vasoconstriction after observing an attenuated contraction in obese OS coronaries compared with lean control arteries. Using vasodilators that induce relaxation through endothelium-independent (SNP) and endothelium-dependent (substance P and bradykinin) mechanisms, we examined the vascular reactivity of LAD coronary arteries obtained from CLI ϩ SR-nitrite-treated pigs, CLI ϩ placebotreated pigs, and nonischemic lean control pigs.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, LAD coronary arteries obtained from obese OS had attenuated contraction to KCl and PGF 2␣ compared with Yorkshire nonischemic lean control swine with no significant difference between CLI ϩ SR-nitrite-and CLI ϩ placebo-treated groups. Similar to our findings, Owen et al (38) concluded that obesity augments Ca 2ϩ cycling and smooth muscle vasoconstriction after observing an attenuated contraction in obese OS coronaries compared with lean control arteries. Using vasodilators that induce relaxation through endothelium-independent (SNP) and endothelium-dependent (substance P and bradykinin) mechanisms, we examined the vascular reactivity of LAD coronary arteries obtained from CLI ϩ SR-nitrite-treated pigs, CLI ϩ placebotreated pigs, and nonischemic lean control pigs.…”
Section: Discussionsupporting
confidence: 92%
“…[21][22][23][24][25] Takaoka et al found elevated expression of proinflammatory genes and lower adiponectin expression in the perivascular adipose tissue of obese mice and concluded that this contributed to exaggerated neointimal formation after arterial injury. 26 Chatterjee et al also found elevated proinflammatory gene expression and diminished adiponectin expression in the perivascular adipose tissue surrounding diseased human coronary arteries.…”
mentioning
confidence: 99%
“…H 2 O 2 , a molecule within the reactive oxygen species (ROS) family, has been proposed to serve as a pivotal vasodilator in coronary flow regulation in human, canine, porcine, and murine coronary vasculature [19,[22][23][24][25][26]. NADPH oxidases (Nox) are the major source of ROS in the vasculature that plays both physiological and pathophysiological roles in the control of vascular tone [27][28][29].…”
Section: Introductionmentioning
confidence: 99%